Pengaruh Media Sosial Terhadap Pola Komunikasi Kyai-Santri Pondok Pesantren Miftahul Huda Manonjaya 2012-2020 - Risma Nahwa Abdilah; Suparman Suparman (UIN Sunan Gunung Djati Bandung, 2022)
The presence of social media as a development of modern technology that affects the pattern of communication in socializing. This study discusses the communication between kyai and santri in learning whether it is influenced by social media as a popular communication tool since several years ago. By using a qualitative approach and data results showing that the Miftahul Huda Manonjaya Islamic Boarding School as the basis of a salafi pesantren is not touched in the slightest by social media in recitation activities or other pesantren activities. The Miftahul Huda Manonjaya Islamic Boarding School still embraces the traditions of its pesantren so that in all activities it still uses traditional methods, without being influenced by outside culture. This is what makes the Miftahul Huda Manonjaya Islamic Boarding School a pure salaf-based Islamic boarding school located in West Java.